If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1m = 6 Solving 2 + -1m = 6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1m = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 6 + -2 -1m = 6 + -2 Combine like terms: 6 + -2 = 4 -1m = 4 Divide each side by '-1'. m = -4 Simplifying m = -4
| 18x-6=35+14x | | y=1x(2x^2) | | 2x^2+14x=7x+4 | | 6+a=-4a-9 | | 6w+5-2w=25 | | y=-k^2+4k+6 | | p-1=5p-1+3p-8 | | 16d+29d+13d=200 | | 9-9x=12x+6 | | 14-2y+5=-2y+9 | | 24-6k=-2(-2+5k) | | 20x^2-48x-36=0 | | -24x-6=3x+27 | | 24-6k=2(-2+5k) | | -5(11-3x)=15 | | 6x(x+3)=30 | | -4+2y=-30 | | -9n+7=-10n | | 80=2(8+a) | | 3(175x+152)= | | 10.5+0.5p=0.9p+5.3 | | 14-(2y+5)=-2y+9 | | 0.4xk=40 | | 2(x-2)-2=10 | | -5f+9=-3f-9 | | 16=d-1212 | | 2v-5v=18 | | 22x+10+80=180 | | -3xk=-18 | | 78=-10x-32 | | 15-20x=16x+2 | | 7+10n+12=11n+1+7 |